Srikandi life fragments transformation in Panah Asmara Srikandi and Kekasih Musim Gugur novels - Nastikaputri, Nadhila Hibatul; Pratama, Frengki Nur Fariya; Prawiroatmodjo, Sudibyo (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2024)
One of the wayang (traditional Javanese puppetry) stories that continues to be explored by local and national Indonesian writers for storytelling is the tale of Srikandi. This research aims to identify the forms of transformation of Srikandi's life fragments in two contemporary Indonesian novels titled Panah Asmara Srikandi and Kekasih Musim Gugur using Julia Kristeva's intertextuality theory. This research is a qualitative descriptive study with data in the form of verbal symbols. The data were analysed using suprasegmental analysis and intertextual analysis methods. The research results indicate that (1) there is homology between Srikandi's transgender identity in the novel Panah Asmara Srikandi and Srikandi's bisexuality in Kekasih Musim Gugur with the character Bambang Kandihawa in the wayang narrative; (2) there are differences in the forms of transformation of Srikandi's life fragments in Panah Asmara Srikandi and Kekasih Musim Gugur due to differences in the authors' motives; (3) in Panah Asmara Srikandi which is an amplification of the wayang narrative and an affirmation of the author towards the wayang story, there is a process of transposition of the wayang text through transformation while retaining the story's conventions. Meanwhile, in Kekasih Musim Gugur which is an adaptation of the wayang narrative and a restoration by the author, there is a process of transposition of the wayang text through transformation by altering the story's conventions.